Reproducibility of the Rocabado pain map. Issue 2 (4th March 2023) - Espinoza, Sebastián; Varela, Daniela; Richter, Carla; Sepúlveda, Gabriela; Marfull, Norman
ABSTRACT: Objective: This study aimed to demonstrate the reproducibility of the Rocabado pain map (RPM) through its application by different evaluators. Methods: Forty participants (18–45 years old) were evaluated. The examiners applied RPM by searching for painful areas, and their intensities were measured through the visual analog scale (VAS). In addition, presence and degree of joint laxity were estimated. Results: Reproducibility values for antero-inferior synovial (zone 1), lateral ligament (zone 3), temporomandibular ligament (zone 4), posterior-inferior synovial (zone 5), and posterior ligament (zone 7) showed high intraclass correlation (ICC) values (above 0.7). Anterior-superior synovial (zone 2) and posterior-superior synovial (zone 6) showed ICC values above 0.4. Discussion: RPM is reproducible. A "fair" concordance according to Fleiss's criteria in zone 2 (ICC 0.42) and zone 6 (ICC 0.64) might be explained by the difficulties involved in moving the condyle from the upper synovial (zones 1, 5) to the lower synovial (zones 2, 6).